压电-摩擦电耦合感应材料的制备方法和应用 (2023)
本发明公开了一种压电-摩擦电耦合感应材料的制备方法和应用，该制备方法包括如下步骤：S1：将羟丙基纤维素、壳聚糖、碳纳米管溶于酸性溶液中，制得羟丙基纤维素/壳聚糖/碳纳米管溶液；S2：将羟丙基纤维素/壳聚糖/碳纳米管溶液流延在聚四氟乙烯底衬上干燥，得到压电-摩擦电耦合感应材料。本发明的感应材料采用HPC、CTS和CNT以流延法来制备压电-摩擦电耦合感应材料的正极且兼具备压电性能的薄膜，具有优异的机械性能和信号转化性能。 The invention discloses a preparation method and application of a piezoelectric-triboelectric coupling induction material, and the preparation method comprises the following steps: S1, dissolving hydroxy propyl cellulose, chitosan and carbon nanotubes in an acidic solution to prepare a hydroxy propyl cellulose/chitosan/carbon nanotube solution; and S2, casting the hydroxy propyl cellulose/chitosan/carbon nanotube solution on a polytetrafluoroethylene substrate, and drying to obtain the piezoelectric-triboelectric coupling sensing material. According to the sensing material, the HPC, the CTS and the CNT are adopted to prepare the positive electrode of the piezoelectric-triboelectric coupling sensing material through a tape casting method, and a film with piezoelectric performance is also prepared, so th